ChemInform Abstract: Synthesis and Characterization of Two Quaternary Uranium Tellurides, RbTiU3Te9 and CsTiU3Te9. Issue 41 (7th October 2014) - Ward, Matthew D.; Mesbah, Adel; Lee, Minseong; Malliakas, Christos D.; Choi, Eun Sang; Ibers, James A.
Abstract Black crystals of the title compounds are prepared by solid state reactions.